Interval Methods for Solving Nonlinear Constraint Satisfaction, Optimization and Similar Problems From Inequalities Systems to Game Solutions - Kubica, Bartłomiej Jacek (Studies in Computational Intelligence, 2019)
This book highlights recent research on interval methods for solving nonlinear constraint satisfaction, optimization and similar problems. Further, it presents a comprehensive survey of applications in various branches of robotics, artificial intelligence systems, economics, control theory, dynamical systems theory, and others. Three appendices, on the notation, representation of numbers used as intervals' endpoints, and sample implementations of the interval data type in several programming languages, round out the coverage.